Entropy Analysis within Rotating Cylinders of Annulus for Giesekus Viscoelastic Fluid - Mehdi Moayed Mohseni (Journal of Petroleum Science and Technology, 2020)
Entropy analysis, along with convective heat transfer within rotating cylinders of the annulus, is presented using a purely analytical approach for Giesekus rheological model. Two different types of boundary conditions are considered: (a) the constant and different temperature at walls, (b) constant heat flux at the outer wall, and constant temperature at the inner wall. Also, the derived velocity and temperature profiles are coupled in the entropy equation for obtaining the volumetric entropy-generation and the Bejan number expressions. Moreover, the effects of Deborah number (De), mobility factor (α), group parameter (Br/Ω), Brinkman number (Br), and velocity ratio (β) on the above parameters are investigated. Ultimately, results indicate that increment of Brinkman number and group parameters increases irreversibility except when both cylinders rotate with identical angular velocity in the same direction.